郭宝崑历史剧研究 = A study of historical plays of Kuo Pao Kun. - Poh, Qinyu (2008)
本论文通过将郭宝崑 1995 年至 2002 年剧场划分入历史剧的类型，希望对他的剧场进行更深入的研究。针对郭宝崑剧场是失败历史剧或是纯粹反历史剧的多方讨论， 笔者认为应该重新审视划分历史剧的依据，并提议有效地运用类型研究来拓展评论。 在论文的第一部分，笔者借助了新历史主义的理论，分析文学及（作为学科的） 历史两者之间随着时代变迁而不断调整的关系。 在分析的过程中，笔者将引进叙述这个现代概念，而所涉及的课题包括了， 故事是否能够在想象的同时勾勒出绝对的事 实，故事如何能够以科学的素材及写实的剧场表现方式来忠于事实地重演所发生过的事件，故事与事件怎样相互纠结并对对方产生影响等等。不过，焦点还是会放在探 讨，郭宝崑如何通过涵盖过去所可能发生的不同版本，还有使用未经证实的素材以及采用试验性的剧场表现方式，来拒绝使自己 1995 年至 2002 年的剧场贬低成为学科历 史的附属品。郭宝崑剧场与过去的互动，也会牵引出一项发现，即郭宝崑所处的边缘位置如何给予他一个较开阔的视野去看待过去。 论文的第二部分则将重点摆在郭宝崑的编剧及执导能力，看他怎样让他的剧场在消费经济的冲击下持续生存，同时又能确保他在新加坡社会政治领域中保有活跃公民 或知识分子所应具有的发言权。因此，笔者也运用了一些政治、文化及表演方面的理论。而将郭宝崑 1995 年至 2002 年剧场，同他其他阶段的剧场、其他历史剧，进行比 较，则为他戏剧事业的发展和他在新加坡戏剧圈子的价值，注入新观点。 This thesis aims to have a better understanding of Kuo Pao Kun’s plays from year 1995 to 2002 through the classification of them into the genre of history plays. The disputed discussion of Kuo Pao Kun’s plays being an unsuccessful history play or an anti-history play have led to the reconsideration of the definition of history play and the suggestion of ulitising genre study in criticism effectively. In the first part of the thesis, the New Historicism theory has been applied to analyse the changing relationship of literature and History (as in the subject of research). During the analysis, issues regarding whether fiction should protray Truth amidst the imagination, how fiction can reenact events truthfully using scientific sources or realistic dramatic techniques, how fiction and events interwine to influence each other through the introduction of the post modern concept of narratives, etc has been touched on. However, the main focus is on how Kuo Pao Kun refuses to turn his plays from year 1995 to 2002 into a subsidiary of History, by including different possible versions of the past and using non-proven sources or experimental dramatic techniques. The interaction between Kuo Pao Kun’s plays and the past has led to a finding of how the marginalized position of Kuo Pao Kun enabled him to view the past from a broader perspective. The second part of the thesis zooms into the script writing and directing of Kuo Pao Kun which enables his plays from year 1995 to 2002 to survive in the economy of consumerism while allowing him to have a voice of an active citizen or intellectual in the Singapore socio-political aspect. Hence, political, cultural and performance theories have been employed. Comparison with his previous plays and other history plays will also provide insight to the development of his drama carreer and his value in the Singapore drama circle.